Platelet-Rich Plasma Supplemented Revascularization of an Immature Tooth Associated with a Periapical Lesion in a 40-Year-Old Man - Ganesh Ranganath Jadhav; Naseem Shah; Ajay Logani (Hindawi Limited, 2014)
The present case report is the first of its kind that documents the successful outcome of "revascularization," a regeneration-based treatment protocol in a mature adult patient. It belies the myth that "revascularization" should only be done in children and young, adolescent patients. The misconception that stem cells number as well as viability in older age group patients will not allow revascularization to be successful is also contradicted by this case. The paper highlights all the mechanisms that come into play and the enhancing of regenerative response by supplementation with platelet-rich plasma (PRP).